KREDIBILITAS MAHKAMAH KONSTITUSI PASCA PUTUSAN MK NOMOR: 90/PUU-XXI/2023 (Faculty of Law, University of Palembang, 2024)
Constitutional Court Decision Number 90/PUU-XXI/2023 was decided, relating to the requirement that presidential and vice presidential candidates be at least 40 years old. The basis for the lawsuit is based on Law no. 7 of 2017 concerning General Elections as a material test and juridical basis for the age of presidential and vice presidential candidates. There were many pros and cons regarding the results of the decision, resulting in various reactions from the public who felt they were not satisfied with the results of the decision. So the problem of this research is, how is the credibility of the Constitutional Court after the Constitutional Court decision Number 90/PUU-XXI/2023 in terms of the judge's decision making technique, using normative juridical methods, with the research results that the credibility of the Constitutional Court after the Constitutional Court decision Number 90/PUU-XXI/2023 is reviewed The judge's decision-making techniques reduce public trust in the Constitutional Court as an independent state institution. As for Decision Number 90/PUU-XXI/2023, the Constitutional Court judges prioritized syllogism techniques and paid less attention to analytical and equatable techniques so that the credibility of the Constitutional Court as an independent public institution experienced a decline in credibility in the eyes of the public.